Effect of urea and tmao on lipid bilayers - Valerio J.; Bernstorff S.; Funari S.S. (European Pharmaceutical Journal, 2017)
We study the effect of the osmolytes, Urea and trimethylamine-N-oxide (TMAO) on POPE (1-palmitoyl-2-oleoyl-sn-glycero-3- phosphoethanolamine) lipid membranes using SAXS/WAXS and DSC. Their antagonist effect is observed with TMAO stabilizing and Urea destabilizing the lipid bilayer, as seen by others in earlier researches.